LIS1, a glyco-humanized swine polyclonal anti-lymphocyte globulin, as a novel induction treatment in solid organ transplantation - Rousse, Juliette; Royer, Pierre-Joseph; Evanno, Gwénaëlle; Lheriteau, Elsa; Ciron, Carine; Salama, Apolline; Shneiker, Françoise; Duchi, Roberto; Perota, Andrea; Galli, Cesare; Cozzi, Emmanuele; Blancho, Gilles; et al. (Frontiers in Immunology, 2023)
Anti-thymocyte or anti-lymphocyte globulins (ATGs/ALGs) are immunosuppressive drugs used in induction therapies to prevent acute rejection in solid organ transplantation. Because animal-derived, ATGs/ALGs contain highly immunogenic carbohydrate xenoantigens eliciting antibodies that are associated with subclinical inflammatory events, possibly impacting long-term graft survival. Their strong and long-lasting lymphodepleting activity also increases the risk for infections. We investigated here the in vitro and in vivo activity of LIS1, a glyco-humanized ALG (GH-ALG) produced in pigs knocked out for the two major xeno-antigens αGal and Neu5Gc. It differs from other ATGs/ALGs by its mechanism of action excluding antibody-dependent cell-mediated cytotoxicity and being restricted to complement-mediated cytotoxicity, phagocyte-mediated cytotoxicity, apoptosis and antigen masking, resulting in profound inhibition of T-cell alloreactivity in mixed leucocyte reactions. Preclinical evaluation in non-human primates showed that GH-ALG dramatically reduced CD4+ (p=0.0005,***), CD8+ effector T cells (p=0.0002,***) or myeloid cells (p=0.0007,***) but not T-reg (p=0.65, ns) or B cells (p=0.65, ns). Compared with rabbit ATG, GH-ALG induced transient depletion (less than one week) of target T cells in the peripheral blood (<100 lymphocytes/L) but was equivalent in preventing allograft rejection in a skin allograft model. The novel therapeutic modality of GH-ALG might present advantages in induction treatment during organ transplantation by shortening the T-cell depletion period while maintaining adequate immunosuppression and reducing immunogenicity.